The Influence Of Self-Efficacy And Scientific Literacy On Learning Motivation In Biology Learning Among Grade Xi Students Of Man Enrekang - Rizqa Amalia; Andi Tenri Ola Rivai; Muh. Syihab Ikbal; Eka Damayanti (UNIVERSITAS KHAIRUN, 2026)
This study aimed to analyze the influence of self-efficacy and scientific literacy on the learning motivation of Grade XI students at MAN Enrekang in biology learning. This research employed a quantitative approach with an ex post facto design. The sample consisted of 91 students selected through proportional sampling. The research instruments included a self-efficacy questionnaire, a learning motivation questionnaire, and a scientific literacy test. Data were analyzed using descriptive statistics and multiple linear regression analysis. The results showed that students’ self-efficacy was in the moderate-to-good category, learning motivation was in the good category, and scientific literacy was at the basic proficiency level. Inferential analysis revealed that self-efficacy had a significant effect on learning motivation with a contribution of 32.9%, whereas scientific literacy showed a low contribution of 1.5%. Simultaneously, self-efficacy and scientific literacy accounted for 34.8% of learning motivation. These findings indicate that self-efficacy is a more dominant factor in enhancing students’ learning motivation compared to scientific literacy. Therefore, strengthening self-efficacy through instructional strategies that support self-confidence, mastery experiences, and positive learning environments should become an important concern in biology learning.